Modelling and simulation of batch adsorption of malachite green using groundnut shell waste-based activated carbon. (5th August 2019) - Dahlan, Irvan; Kit, Kan Chee
Modelling and simulation of batch adsorption in malachite green dye removal using activated carbon prepared from groundnut shell waste was studied. Mathematical model was developed based on a two-resistance model which included external mass transfer coefficient and pore diffusion coefficient that controls the mass transfer process in batch adsorption. MATLAB program was written to solve ordinary differential equation from the model and to estimate mass transfer parameters by matching the simulation data with the experimental data from literature. From the results, it was found that the external mass transfer coefficient k f and pore diffusion coefficient D p were estimated to be 6.2054 × 10 −2 m/s and 2.2660 × 10 −10 m 2 /s, respectively. Using the estimated parameters, simulation results showed that the model provided good correlation with the experimental data based on different initial concentrations. The estimated parameters were used to study the adsorption of dye under different variables such as initial dye concentration, volume of dye solution, adsorbent particle size and mass of adsorbent. It was concluded that the dye removal efficiency was higher for lower initial dye concentration, higher mass of adsorbent, lower volume of dye solution and smaller adsorbent particle size.